The unequal spirit of the protestant reformation: Particularism and wealth distribution in early modern Germany - Felix S. F. Schaff (European Historical Economics Society (EHES), 2023)
This paper studies the impact of the Protestant Reformation on wealth distribution and inequality in confessionally divided Germany, between 1400 and 1800. The Reformation expanded social welfare, but provided it in a particularistic way to insiders only. This gave Protestantism an ambiguous character in terms of redistribution and its impact on inequality. I develop a theoretical framework of this trade-off between welfare expansion and particularistic provision, and test its implications empirically, using a Difference-in-Differences and an Instrumental Variable strategy. In line with the theoretical framework, I document that the Reformation exacerbated inequality overall, by making marginal poor people relatively poorer. The result is driven by the introduction of new particularistic poor relief policies in Protestant communities. Protestantism is an underappreciated driver of preindustrial inequality, long before the onset of industrialisation and modern economic growth.
Keywords: D31; H23; I38; N33; 330; Wealth; Poverty; Inequality; Political Economy; Protestantism; Welfare; Germany